1984
DOI: 10.1007/bf01869201
|View full text |Cite
|
Sign up to set email alerts
|

Detergent sensitivity and splitting of isolated liver gap junctions

Abstract: Isolated rat liver gap junctions were split by two methods. In the first method, isolated gap junctions were stabilized by cross-linking their cytoplasmic surfaces with glutaraldehyde under conditions that prevented the entry of glutaraldehyde into the "gap" region. The "stabilized" junctions were then split in the junctional gap with SDS. In the second procedure, unfixed gap junctions were split by incubation in urea-containing solutions. Junctional splitting was monitored by electron microscopy of thin secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 30 publications
1
22
1
Order By: Relevance
“…The difficulty was then to solubilize the 41-kDa gap-junction protein in such a way that the nature and the concentration of detergents used did not prevent the specific antigen-antibody recognition on the immunomatrix. Manjunath et al (1984b) and Manjunath and Page (1986) had previously shown that liver and heart gap junctions were resistant to non-ionic detergents and insoluble in 8 M urea. More recently however, MP70 was extracted from lens fibre gap junctions using the non-ionic detergent Nonidet P-40 (Kistler and Bullivant, 1988) and liver gap junctions were shown to be solubilized with digitonin and/or octylglucoside (Mazet and Blattmann, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty was then to solubilize the 41-kDa gap-junction protein in such a way that the nature and the concentration of detergents used did not prevent the specific antigen-antibody recognition on the immunomatrix. Manjunath et al (1984b) and Manjunath and Page (1986) had previously shown that liver and heart gap junctions were resistant to non-ionic detergents and insoluble in 8 M urea. More recently however, MP70 was extracted from lens fibre gap junctions using the non-ionic detergent Nonidet P-40 (Kistler and Bullivant, 1988) and liver gap junctions were shown to be solubilized with digitonin and/or octylglucoside (Mazet and Blattmann, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…First, the liverjunction plaques were totally dissociated and solubilized by the detergent mixture digitonin/ n-octyl-P-D-glucoside, whereas none of the detergents used previously (Triton X-100, Nonidet P-40, sarkosyl, Chaps) was known to split liver gap junctions (Manjunath et al, 1984). Second, the aggregation state of the gap junctions in proteoliposomes could be controlled through reconstitution conditions, and the structure of the resulting clusters are identical to the native structure (Mazet and Mazet, 1990).…”
mentioning
confidence: 99%
“…We prepared gap junctions from rat livers by simplifying our previously published method (Manjunath et al, 1984a) as follows: The liver from a single adult rat (Sprague-DawIey, of either sex, 300-350 g) was excised and placed in an ice-cold solution (medium A) whose composition was 1 mM NaHCO~, 1 mM PMSF, 0.1 mM p-hydroxymercuribenzoate (PHMB), pH 8.2. In this medium, the tissue was first minced and homogenized for 30 sec with a VirTis homogenizer set at maximal speed, then homogenized further for 5-6 sec with a Tissuemizer (Tekmar Instruments, Model SDT 100 EN), also set at maximal speed.…”
Section: Unproteolyzed Rat Liver Gap Junctionsmentioning
confidence: 99%
“…The cytoplasmic surface component is cleaved during isolation by an alkaline serine proteinase released from the granules of mast cells present in the heart, a proteolytic reaction that is inhibitable with phenylmethylsulfonyl fluoride (PMSF) (Manjunath, Goings & Page, 1985). Gap junctions isolated from rat liver, which lack this component even when isolated with PMSF, are devoid of cytoplasmic surface fuzz (Manjunath, Goings & Page, 1984a) and cytoplasmic surface particles (Shibata et al, 1985). These observations, as well as differences in amino acid sequences (Nicholson et al, 1985), suggest that the protein compositions of cardiac and liver gap junctions differ in important respects.…”
Section: Introductionmentioning
confidence: 99%